Obstacles and Challenges in the Development of MSMEs: Case Study - Irwan Sugiarto (Budapest International Research and Critics University, 2018)
This study aims to find out and analyze MSMEs rigorously to develop their business. The method used is a qualitative method with a descriptive approach. Obstacles to developing MSMEs include quality, human resources, capital, infrastructure, and technology. This problem causes a price decline in providing counseling and from the banking world. Therefore, this is part of various parties that are very helpful for the development of MSMEs, especially those in rural areas.